Analysis of competitive binding of several metal cations by graphene oxide reveals the quantity and spatial distribution of carboxyl groups on its surface. Issue 4 (5th January 2018) - Amirov, Rustem R.; Shayimova, Julia; Nasirova, Zarina; Solodov, Alexander; Dimiev, Ayrat M.
Abstract : GO contains two different types of binding sites, bonding to which results either in high or low NMR relaxivity of resulted Gd 3+ –GO and Mn 2+ –GO solutions. Abstract : The sorption capacity of graphene oxide (GO) toward different metal cations has been the subject of several recent studies. However, the reported quantitative data are controversial, and the mechanism of chemical bonding between GO and metal cations is poorly understood. Clarifying these questions can eventually help to reveal the fine chemical structure of GO that remains ambiguous. In this work, we study the binding of Gd 3+ and Mn 2+ by GO in the presence of several competing metal cations by the 1 H NMR relaxation method. As a general trend, the efficiency of the metal cations to bind to GO increases with ionic charge, and depends on their ability to form coordinate-covalent bonds with GO oxygen groups. The efficiency of the competing metal cations to "replace" Gd 3+ and Mn 2+ increases in the order Na + < Cs + < Ca 2+ < Sr 2+ < Ga 3+ < Lu 3+ . GO contains two different types of binding sites, bonding to which results in either high or low NMR relaxivity of the resulting Gd 3+ –GO and Mn 2+ –GO solutions. Gd 3+ and Mn 2+, being replaced from the high-relaxivity sites by the large excess of competing cations, are not released into the bulk solution, but only migrate to the low-relaxivity sites, remaining covalently bonded to GO. The absolute majority of the existing carboxyl groups in GO are located at tiny few-carbon-atom-vacancy defects on the major planes. The density of these vacancy defects is estimated as one per every 200 carbon atoms.